Designing Strategies for University Students’ Writing Skill - Ismiati Ismiati; Erlin Pebriantika (Journal of Languages and Language Teaching, 2020)
In the process of teaching and learning English writing skill, some strategies which are considered appropriate for a certain group of learners, may not suitable for other groups as each group has its own problems and needs in writing. Therefore, teaching learning strategies for English writing requires to be continuously developed. This study aims to design strategies based on the students’ writing needs and problems as the development of the previous common implemented strategies in writing course classes at English Study Program of Cordova University, West Sumbawa Regency. The research subjects were students who are active studying English as their major specialization and lecturers who have been teaching English writing course in academic year 2018/2019.The result shows that the previous strategies give little significant impact toward the students’ writing skill progress. For the reasons, new strategies were designed and recommended to be continuously implemented for teaching and learning writing courses and involved in curriculum at English Study Program, Cordova University. Those strategies are (1) Collaborative Writing Strategy. (2) Combining Diary and Guided Writing Strategy. (3) Additional credit hours for writing course classes (4). Graded writing course classes need to be continuously taught by the same lecturer